1997
DOI: 10.1007/s002880050590
|View full text |Cite
|
Sign up to set email alerts
|

Coherent description of $D^{*\pm}$ production in $e^+e^-$ and low- $Q^2$ $ep$ collisions

Abstract: We present new sets of fragmentation functions for D * ± mesons, both at leading and next-to-leading order. They are determined by fitting LEP1 data on inclusive D * ± production in e + e − annihilation. In one of the sets, we take the charm-quark fragmentation function to be of the form proposed by Peterson et al. and thus obtain updated values of the c parameter and the c → D * + branching ratio. The new fragmentation functions lead to an excellent description of other e + e − data with centre-of-mass energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 19 publications
6
70
1
Order By: Relevance
“…The coefficient d i→n (x, µ 0 ) at the initial scale µ 0 = 2m c involves only momenta of order m c , and can thus be calculated within NRQCD in powers of α s (µ 0 ). The evolution of the FF D i→H (x, µ 0 ) up to higher fragmentation scales µ = M T is ruled by the timelike Altarelli-Parisi (AP) equations, which may be conveniently solved in x space [17]. The relative importance of the various terms in Eqs.…”
Section: Theoretical Inputmentioning
confidence: 99%
“…The coefficient d i→n (x, µ 0 ) at the initial scale µ 0 = 2m c involves only momenta of order m c , and can thus be calculated within NRQCD in powers of α s (µ 0 ). The evolution of the FF D i→H (x, µ 0 ) up to higher fragmentation scales µ = M T is ruled by the timelike Altarelli-Parisi (AP) equations, which may be conveniently solved in x space [17]. The relative importance of the various terms in Eqs.…”
Section: Theoretical Inputmentioning
confidence: 99%
“…The parameter ε c is related to the heavy quark mass (M c for charm quark) by ε c = Λ 2 /M 2 c and Λ stands for a hadronic scale. The PFF at scale µ > µ 0 can be given by solving the DGLAP equations, which is complicated in numerical calculations and currently there is no parametrization forms available as for the light quark fragmentation function [36]. To simplify the numerical calculations, we choose µ 0 = Q as the first step for numerical calculations and then obtain D D c (z, Q) and D D g (z, Q) according to Eq.…”
Section: The Virtual Corrections In Eq (35) Can Be Obtained Via Unitmentioning
confidence: 99%
“…After considering higher order contributions, the inclusive tensor can be written as [31,[34][35][36][37] …”
Section: Generalized Factorizationmentioning
confidence: 99%
“…On the one hand, at NLO, the cross section dσ/dx of e + e − annihilation becomes negative in the upper x range, at x ∼ > 0.9 [see Fig. 4(a)], where the data is very precise, so that a low-quality fit is obtained unless this x range is excluded by hand [34,35]. On the other hand, the LO and NLO predictions for other types of processes, such as photoproduction in ep scattering [see Fig.…”
Section: Inclusive B-meson Productionmentioning
confidence: 99%
“…The attempt to split the B-meson FFs into a so-called perturbative FF (PFF) and a nonperturbative remainder is interesting in its own right. However, detailed analysis for D * ± -meson FFs [34] revealed that such a procedure leads to deficient results in practical applications. On the one hand, at NLO, the cross section dσ/dx of e + e − annihilation becomes negative in the upper x range, at x ∼ > 0.9 [see Fig.…”
Section: Inclusive B-meson Productionmentioning
confidence: 99%